Citrus soil management can reduce the deterioration of soil conditions and improve sustainability production - Goñi, C.; Otero, A. (Agrociencia Uruguay, 2012)
Long term traditional herbicide uses for soil management brings soil compaction, crusting, poor infiltration and week rooting trees, leading to orchard deterioration and poor soil sustainability. The amelioration of the soil properties and plant growing condition was evaluated on a young rainfed citrus orchard of Valencia late (NVA 036) grafted on Poncirus trifoliate rootstock during three years, planting on an Argisol Districo Ocrico soil. A combination of organic mulch (rows) and sod cultivation (between rows) were applied. A 75 cm wide row with two organic mulch sources was used: a) composted Eucalyptus wood chip (52 kg m-2) with a C/N ratio of 1.5, and b) commercial compost (30 kg m-2 ) with a C/N of 10. Between row treatments sod consisted in a) Ornithopus compressus, and b) Lolium multifl orum. The traditional herbicide application in the row and the spontaneous vegetation between rows were the control. Soil organic matter, nitrogen mineralization potential and soil biomass have not changed in the row for the first 4 years. However, the use of mulch significantly reduces the amplitude of soil temperature, at the 15 cm depth and holds up soil water availability more time than the herbicide application. During summer drought, stem water potential of the trees under mulch varies between -1.4 to -2.2 MPa compared with the - 3.5 to -3.8 MPa with the herbicide. Sod dry matter accumulation was variable between years, and has not significant effect in the physical and chemical properties to the present. Mulches have generated better tree growing conditions than the herbicide, resulting in significant increments in tree vigor, precocity, and yield. Wood chip mulch has increased 42% the accumulated crop yield, enhances fruit color and reduced the need of weed control. Mulch application seems to be a promising soil management measure for citrus young trees in this soil and climate conditions.